PW 0255 Stragic framework for drowning prevention and water safety in the western cape province of south africa. (November 2018) - Simons, Abigail; Singh, Robyn; Saunders, Colleen; Niekerk, Ashley van
Abstract : Drowning is a serious and neglected public health threat, especially in Africa where, despite high rates of drowning, few coordinated drowning prevention initiatives have been reported. In South Africa, there is an emerging research and advocacy platform for water safety and drowning prevention, especially in the Western Cape Province. Drowning mortality in the Western Cape is reported at 3.2 per 100 000 population. Prevention responses have been characterised by insufficient collaboration; inadequate information or surveillance systems; limited local research capacity; insufficient resource allocation; and inadequate monitoring of existing interventions. The overall aim of this study was to support the prioritisation of intervention programmes to prevent drowning and promote water safety through evidenced-based research. A framework was developed through a process that included a review and multi-method analysis of the epidemiology of drowning in the Western Cape, policy, intervention descriptions and drowning research; and in-depth interviews with local intervention and policy experts. The Strategic Framework highlights key safety intervention recommendations that emerged through this process, targeting the prevention of risk factors specific to priority groups and settings, the mobilisation of key local populations, and the strengthening of supportive institutions and decision-making authorities. The Strategic Framework has prioritised seven objectives: 1) establish a provincial information strategy and systems, based on existing platforms, 2) strengthen the advocacy and enforcement of priority policy measures, 3) promote multi-sectoral partnerships and water safety collaborations, 4) strengthen institutional prevention capacity, 5) strengthen public and specialised education and community awareness, 6) institute priority barrier interventions, and 7) develop supportive Infrastructural interventions.